Characterization of Goat Production Systems in the Northern Dry Forest of Peru Using a Multivariate Analysis - Temoche Socola , Victor Alexander (2025)
The document states that the article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license.